"I've Never Told Anyone": A Qualitative Analysis of Interviews With College Women Who Experienced Sexual Assault and Remained Silent. (July 2022) - Caron, Sandra L.; Mitchell, Deborah
The purpose of this study was to gain an understanding of the decision made by some college women who are raped to tell no one . In-depth interviews were conducted with 15 college women between the ages of 19-24 who had never shared their sexual assault with anyone prior to speaking to the researchers. This study provides a systematic investigation of the factors underlying women's decisions to remain silent. The knowledge and understanding gained from these in-depth interviews offer insight for individuals and institutions to support these students and for the development of future efforts encouraging women survivors to tell someone.